Aid in Education: A study of Nepal - Deori, Vijoyeta (International Journal of Psychosocial Rehabilitation, 2020)
Nepal being one of the least developed countries in the world is dependent on aid from other nations and external agencies. Since the inception of the modern education system in Nepal, aid has been pouring in, but the impact of education on the overall development of the nation does not commensurate with the amount invested in the education system. The sheer amount of aid going by the amount given by outside agencies is very impressive. But looking at the final details at the nature and amount of aid tells somewhat a different story. Furthermore, the amount is also found to be different in different sources. The amount publicised by the agencies very often does not match to the amount disclosed by the government of Nepal. Superficially, the problem and solution of Nepal‘s lack of progress and development, including educational, appear very simple. Nepal, being a poor country, is not in a position to provide all the resources needed; donor agencies and countries try to bridge the gap. But despite the long relationship between Nepal and donors and resultant foreign aid, it does not seem to be working sufficiently enough for the people of Nepal. In this article, the various factors that influence the nature of aid in Nepal's education system will be dealt with.